FcεRI γ-Chain Negatively Modulates Dectin-1 Responses in Dendritic Cells - Pan, Yi-Gen; Yu, Yen-Ling; Lin, Chi-Chien; Lanier, Lewis L.; Chu, Ching-Liang (Frontiers in Immunology, 2017)
The inhibitory effect of immunoreceptor tyrosine-based activation motif (ITAM)-containing adapters DAP12 and Fc epsilo RI gamma-chain (FcR gamma) has been found in many immune functions. Herein, we have further explored the role of these adapters in C-type lectin receptor (CLRs) response. We identified that FcR gamma, but not DAP12, could negatively regulate the Dectin-1 responses in dendritic cells (DCs). Loss of FcR gamma or both DAP12 and FcR gamma enhanced the maturation and cytokine production in DCs upon Dectin-1 activation compared to normal cells, whereas DCs lacking only DAP12 showed little changes. In addition, increments of T-cell activation and Th17 polarization induced by FcR gamma-deficient DCs were observed both in vitro and in vivo. Examining the Dectin-1 signaling, we revealed that the activations of several signaling molecules were augmented in FcR gamma-deficient DCs stimulated with Dectin-1 ligands. Furthermore, we demonstrated that the association of phosphatases SHP-1 and PTEN with FcR gamma may contribute to the negative regulation of FcR gamma in Dectin-1 activation in DCs. These results extend the inhibitory effect of ITAM-containing adapters to Dectin-1 response in immune functions, even though Dectin-1 contains an ITAM-like intracellular domain. According to the role of Dectin-1 in responding to microbes and tumor cells, our finding may have applications in the development of vaccine and cancer therapy.